Description of a new species of Pagurus Fabricius, 1775 (Crustacea: Paguroidea: Paguridae) from the Pacific coast of Costa Rica, Central America, with notes on Pagurus albus (Benedict, 1892) - Ayón-Parente, Manuel; Wehrtmann, Ingo S. (Zootaxa, 2019)
A redescription of Pagurus albus (Benedict, 1892) is presented together with a description of a new species of hermit crab, Pagurus pseudoalbus sp. n., from the Pacific coast of Costa Rica. Pagurus pseudoalbus sp. n. differs from P. albus and P. perlatus by the length of antennal acicles, which do not exceed the distal margin of the 4th antennal segment, whereas in the latter two species, the antennal acicles exceed the 4th antennal segment; the antennular peduncle is proportionally longer than the ocular peduncle in the new species compared to P. perlatus, but shorter than in P. albus; the palm of the right cheliped in P. pseudoalbus sp. n. is 1.3 times as long as broad, while in P. albus and P. perlatus it is 1.0 and 1.4 times as long as broad, respectively. Including the new species, the genus Pagurus in the Eastern Tropical Pacific currently includes 16 species.